AKHLAK ATAU ETIKA GURU MENURUT KH AHMAD DAHLAN DAN KH HASYIM ASY’ARI - Moh. Khakim; Muhammad, Devy Habibi (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research is based on the author's concern regarding the recent decline in teacher morals/ethics. Judging from the large amount of coverage regarding the behavior of individual teachers, such as cases of sexual abuse against several students. The aim of this research is to obtain further information regarding the views of K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari regarding the morals and ethics of an educator. The type of research or model used by the author is a type or form of qualitative research, which takes the form of library research, which is carried out by evaluating several related data, either from primary sources (Primary Sources) or secondary sources (Secondary). The findings from the research show that there are fewer differences and more similarities between the views of K.H. Ahmad Dahlan and K.H. Hasyim Asy'ari regarding the ethics of an educator in the context of Islamic Religious Education (PAI). Meanwhile, the apparent dissimilarity between the two of them regarding teacher ethics lies in Kiai Ahmad Dahlan's perspective on the relationship between teachers and students. K.H. Ahmad Dahlan emphasized the importance of educators being open, with the belief that the teaching and learning process can occur in various places and at any time. Not a few of his students became friends in their struggle, highlighting the importance of openness and a close relationship between a teacher and his students. Kiai Hasyim Asy'ari, on the other hand, shows caution, a teacher must maintain his authority. With the existing differences, the author can conclude that if the elements emphasized by Kiai Ahmad Dahlan al-Haj and Kiai Hasyim Asy'ari al-Haj are combined, a teacher's morals or ethics will be formed that are very positive and perfect each other.